Evaluation of Combination Chemotherapy Effect of Platinum, Vincristin, Bleomycin, and Mitomycin C on Cervical Cancer Based upon Apoptosis Description - Hasan, Agus (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To observe the success of platinum, vincristin, bleomycin and mitomycin C (PVB-MMc) combination chemotherapy on cervical carcinoma by evaluating apoptosis feature. Methods: This study was performed at Dr. Wahidin Sudirohusodo Hospital and several other hospitals. The method of this study was prospective longitudinal. Cervical biopsy was performed on 15 cervical carcinoma patients before and after PVB-MMc chemotherapy. Six patients were at early stage and 9 patients were at advanced stage. Biopsy result were sent to pathologic anatomic laboratory to be made into paraffin block and further examined for apoptosis with Tunel method. Data were analyzed by using Wilcoxon Signed Rank test. Results: Study results indicating no significant difference for apoptosis index before and after PVB-MMc chemotherapy for early stage (p=0.463), advance stage (p=0.594), but quantitatively there were increasing apoptosis index before and after chemotherapy. Conclusion: Chemotherapy combination PVB-MMc for cervix carcinoma can increase apoptosis index and give a good response in term of reducing the tumor size although statistically not significant. [Indones J Obstet Gynecol 2012; 36-4: 200-5] Keywords: apoptosis, cervical carcinoma, PVB-MMc combination chemotherapy.